The need for sustainable tourism in an era of global climate change : pathway to a greener future - Singh, Pardeep; Daga, Shikha; Yadav, Kiran; Jain, Abhay (Emerald Publishing Limited, 2024)
In The Need for Sustainable Tourism in an Era of Global Climate Change: Pathway to a Greener Future, the authors delve into the critical transition from traditional to sustainable tourism. This comprehensive work examines the essential policy initiatives required at individual, organizational, national, and global levels to foster sustainable tourism practices. Offering an in-depth analysis of the identification and implementation of green infrastructure, green travel, green hotels, and green energy, the authors argue that its successful implementation can significantly contribute to achieving sustainable development goals and cultivating a green global economy. This will be an indispensable resource for both students and practitioners who wish to understand and promote sustainable tourism in our rapidly changing world.